Existence of positive solutions for a semipositone discrete boundary value problem - Luca, Rodica (Nonlinear Analysis: Modelling and Control, 2019)
We investigate the existence of positive solutions for a nonlinear second-order difference equation with a linear term and a sign-changing nonlinearity, supplemented with multi-point boundary conditions. In the proof of our main results, we use the Guo–Krasnosel'skii fixed point theorem.